2000
DOI: 10.1007/s002610000061
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of adrenal myelolipoma: spiral CT appearance

Abstract: We report the helical computed tomographic findings of a symptomatic giant (11 cm) adrenal myelolipoma with spontaneous extracapsular hemorrhage. Narrow collimation (3 mm) imaging and three-dimensional reconstructions were useful to fully characterize the components and location of the lesion. A literature search showed a striking male and right-sided predominance for spontaneously hemorrhagic myelolipomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 25 publications
0
17
0
3
Order By: Relevance
“…They are usually slow-growing, non-functioning, and asymptomatic. Occasionally, large tumors or those undergoing tumor necrosis or spontaneous hemorrhage may cause flank pain [161,162]. Because these tumors contain large amounts of fat, most myelolipomas are easily recognized on CT. On CT scans, the majority of myelolipomas are well defined and measure 1-4 cm in size.…”
Section: Myelolipomamentioning
confidence: 99%
“…They are usually slow-growing, non-functioning, and asymptomatic. Occasionally, large tumors or those undergoing tumor necrosis or spontaneous hemorrhage may cause flank pain [161,162]. Because these tumors contain large amounts of fat, most myelolipomas are easily recognized on CT. On CT scans, the majority of myelolipomas are well defined and measure 1-4 cm in size.…”
Section: Myelolipomamentioning
confidence: 99%
“…In the case of bilateral myelolipomas, recommendations suggest removal of the larger and more symptomatic side and observation of the contralateral side for as long as possible to avoid lifelong supplementation of steroids [12]. The literature also demonstrates that myelolipomas can grow significantly during the observation period and a few studies have reported spontaneous hemorrhage with minor trauma in these patients [16, 17]. In our case, a bilateral adrenalectomy was performed because bilateral giant myelolipomas were present in our patient with congenital adrenal hyperplasia (CAH), with both masses growing significantly over a period of one year.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a considerable number of ruptured tumors tend to be nonfunctional, and present with acute abdominal pain (19,21,22). Therefore, it is assumed that as the non-functional tumors grow without causing symptoms, tumors tend to undergo necrosis which can increase the risk of rupture.…”
Section: Adrenal Glandmentioning
confidence: 99%